The ‘New Powers’ of Future Modernity - Havelka, Miloš (Dějiny – teorie – kritika, 2009)
With a focus on the chapters about the Early Modern period in Loewenstein’s Víra v pokrok (Faith in Progress), the author discusses the theme of ‘new powers’ on the threshold of the process of modernization in Europe, that is, of disciplining and liberty. He places Loewenstein’s interpretations into the context of more recent socio-historical research and also early works (for example, Bertrand Russell’s Freedom and Organization, 1934), and aims at a description of Early Modern phenomena of civilization with the transformations of external and internal coercion, elements of competition and mutual dependence, the homogenization of man, disciplining as a prerequisite of civil society, and the open, or immanent, future as the spheres of life most proper to human beings.